Prediksi Kesulitan Keuangan dan Kebangkrutan Perusahaan Sektor Properti dan Real Estate dengan Pendekatan Analisis Multivariat Diskriminan - Tasman, Abel; Kurniawati, Tri (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2014)
The objective of this research is to examine the performance of financial ratios to predict financial distress and bankrupty. Sample consist of 32 property and real estate industries which listed in The Indonesia Stock Exchange (IDX) from 2005 until 2012. Sample would be classified into Distress company group and Non Distress company group based on operating profit and economic rentability and each group will be evaluatedÂ by Multivariat Discriminant Analysis. Independent variables consist of 7 financial ratios which are working capital to total asset, current asset to sales, current liabilities to total asset, market value of stock to book value of total debt, sales to total asset, retained earning to total asset and earning before interest and tax to total asset. The result of this research showedÂ that the financial ratios which can be a predictor of financial distress and bankrupty in property and real estate industries was earning before interest and tax to total asset. The result showed accurately prediction as much as 87,5%.